2014
DOI: 10.1021/jp411201k
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering of BiI3 Single Crystals: Enhanced Electrical and Radiation Performance for Room Temperature Gamma-Ray Detection

Abstract: Undoped and Sb-doped BiI 3 (SBI) single crystals are grown via the vertical Bridgman growth technique. Electrical properties, such as resistivity and leakage current, in addition to radiation response measurements are performed on both BiI 3 and SBI single crystal detectors. The resistivity of SBI (2.6310 9 Ω•cm) increases by an order of magnitude compared to that of BiI 3 (1.45 × 10 8 Ω•cm). Furthermore, leakage currents of SBI (10 −2 μA/cm 2 ) decrease by four orders magnitude relative to BiI 3 . The radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 32 publications
4
86
1
Order By: Relevance
“…Angle (degrees) 10 8 literature suggests that it exceeds 10 5 cm -1 above 2 eV. 8 Use of a thinner film or spectroscopic ellipsometry 8 would allow for a more accurate determination of α.…”
Section: θ [Degrees]mentioning
confidence: 99%
See 1 more Smart Citation
“…Angle (degrees) 10 8 literature suggests that it exceeds 10 5 cm -1 above 2 eV. 8 Use of a thinner film or spectroscopic ellipsometry 8 would allow for a more accurate determination of α.…”
Section: θ [Degrees]mentioning
confidence: 99%
“…We grow single crystals by a modified vertical Bridgman method using electrodynamic gradient techniques. 10 We then verify the phase and morphology of the films through X-ray diffraction (XRD) and micrographs. Substrate growth temperature has a strong effect on the orientation and morphology of PVT BiI 3 .…”
mentioning
confidence: 99%
“…62 Han et al reported a route to improve the electron mobility of BiI 3 from 600 cm 2 V 1 s 1 to 1000 cm 2 V 1 s 1 via Sb-doping (determined from time-of-flight measurements). 65 They identified I-vacancies as the major defect in BiI 3 and using DFT calculations proposed that Sb-doping increases the formation energy of iodine vacancies, thus reducing iodine migration through BiI 3 . However, BiI 3 has a large hole effective-mass of 10.39 (Table I), whilst also being known to suffer from severe hole trapping, thus its application in devices may be limited by poor hole transport.…”
Section: -mentioning
confidence: 99%
“…However, BiI 3 has a large hole effective-mass of 10.39 (Table I), whilst also being known to suffer from severe hole trapping, thus its application in devices may be limited by poor hole transport. 18,65 BiOI is another 2D material that has generated interest as a solar absorber based on its promising activity as a photocatalyst. 66 BiOI single crystals have been grown by chemical vapor transport, where their application as a substrate in superconductor devices was studied.…”
Section: -mentioning
confidence: 99%
“…Moreover, its low toxicity, large absorption cross‐section (≈10 5 cm −1 ) in the visible region (400–650 nm), and air‐stable properties have caused BiI 3 to receive more attention recently for use in photovoltaics . Although BiI 3 has been widely studied for use in radiation detection, academic studies of BiI 3 applied in optical detectors are relatively rare. In 2017, Li et al demonstrated BiI 3 nanoplate/WSe 2 p–n diodes with gate‐tunable rectification and a photoresponsivity of 1.67 A W −1 .…”
Section: Introductionmentioning
confidence: 99%